The Influence of Difference Exercise Anaerobic Interval Methods Against The Results of The Shooting Ratio of Underbasket Height and Long Limbs - Satria, Agni Herarta Anindya (Department of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research is to know (1) the difference between the influence of the ratio of anaerobic interval exercise 1:3 exercise, anaerobic interval and the ratio of 1:5 against shooting underbasket results, (2) the difference between the ratio shooting results underbasket height: long legs and high ratio of height: long limbs are low, (3) the influence of the interaction between exercise anaerobic interval ratio and the ratio of height: the length of the limbs results shooting underbasket. This research uses experimental methods with a 2 x 2 factorial design. Based on the results of the analysis of the data shows that: (1) there is a significant influence on the differences between the ratio of anaerobic interval exercise 1:3 exercise anaerobic interval and the ratio of 1:5 against results shooting underbasket, pvalue < 0, 05. Influence of exercise anaerobic interval with the ratio of 1:5 has better results than an anaerobic interval workout with a 1:3 ratio with average results respectively 9 and 8, 43, 43. (2) no difference shooting results significant underbasket between height ratio: the ratio of height and limb length height: long limbs, pvalue < 0.05. Results of shooting underbasket earned by the sample with a ratio of height: the length of the limb with a low category better than the sample with a ratio of height: long limbs with high category with average results each 19.14 and 16.67. (3) there is the influence of the interaction between exercise anaerobic interval ratio and the ratio of height: the length of the limbs results shooting underbasket, pvalue < 0, 10.